Household finances and the "Big Five" personality traits - Sarah Brown; Karl Taylor (Institute for the Study of Labor (IZA), 2011)
We explore the relationship between household finances and personality traits from an empirical perspective. Specifically, using individual level data drawn from the British Household Panel Survey, we analyse the influence of personality traits on financial decision-making at the individual level focusing on decisions regarding unsecured debt acquisition and financial assets. Personality traits are classified according to the 'Big Five' taxonomy: openness to experience, conscientiousness, extraversion, agreeableness and neuroticism. We find that certain personality traits such as extraversion and openness to experience exert relatively large influences on household finances in terms of the levels of debt and assets held. In contrast, personality traits such as conscientiousness and neuroticism appear to be unimportant in influencing levels of unsecured debt and financial asset holding. Our findings also suggest that personality traits have different effects across the various types of debt and assets held. For example, openness to experience does not appear to influence the probability of having national savings but is found to increase the probability of holding stocks and shares, a relatively risky financial asset.
urn:nbn:de:101:1-201201104053
Keywords: C24; D03; D14; 330; Big Five personality traits; financial assets; unsecured debt; Private Finanzplanung; Anlageverhalten; Persönlichkeitspsychologie; Schätzung; Großbritannien